Cases, simulacra, and Semantic Web technologies. (15th November 2011) - Carmichael, P.; Tscholl, M.
Abstract 'Ensemble' is an interdisciplinary research and development project exploring the potential role of emerging Semantic Web technologies in case‐based learning across learning environments in higher education. Empirical findings have challenged the claim that cases 'bring reality into the classroom' and that this, in turn, might provide the basis for an understanding of the role of Semantic Web technologies in case‐based learning environments. We describe how the work of authors including Baudrillard and Deleuze has provided an alternative framework for understanding the relationships between cases and the realities with which they are purportedly associated. We discuss how the idea of the 'simulacrum' has influenced our understanding of learning environments, has informed design and development practices, and has led to a shift in our understandings of the potential affordances of Semantic Web technologies in educational settings.